(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
This research based on a study of samples of elegies from the Early Islam and Umayyad Era from an aesthetic point of view. It examines the presence of one of the aesthetic values, which is the value of the tragic and its manifestations through two main axes: The axis of intellectual construction which means to explain the actions that established the value of the tragic, and the axis of the artistic construction of that value in the studied elegies. That is, researching the most important artistic means - especially linguistic - that poets used to form the intellectual value from the artistic and aesthetic point of view. The purpose of this research is to re-read our ancient poetry well, because it is rich and creative poetry. It accepts multiple readings. It glows and shines by re-highlighting its beauty aspects. The purpose of this research is not to explore all the elegies of Early Islam and Umayyad era, as that is impossible within the limits of this research. But selection here is the basic thing. The selection will be limited to some elegies mentioned in Amali al-Yazidi’s book , because this book included a valuable group selected from the best elegies in ancient poetry[1]. And I chose to select some elegies that had not been fortunate to have been thoroughly studied in the past. * Department of Arabic Language and Literature- Faculty of Letters and Humanities- Damascus University. [1]On its cover bage it was mentioned:" elegies, poems on something else, news and language,…"